Eculizumab Improves Posttransplant Thrombotic Microangiopathy Due to Antiphospholipid Syndrome Recurrence but Fails to Prevent Chronic Vascular Changes. Issue 8 (13th June 2013) - Canaud, G.; Kamar, N.; Anglicheau, D.; Esposito, L.; Rabant, M.; Noël, L.‐H.; Guilbeau‐Frugier, C.; Sberro‐Soussan, R.; Del Bello, A.; Martinez, F.; Zuber, J.; Rostaing, L.; et al.
Abstract: Thrombotic microangiopathy (TMA) is one of the hallmark vascular lesions of antiphospholipid syndrome nephropathy (APSN). These lesions are at high risk of recurrence after kidney transplantation. The complement pathway is thought to be active in this process. We used eculizumab to treat three consecutive kidney transplant recipients with posttransplant TMA due to APSN recurrence that was resistant to plasmapheresis and explored the complement deposition and apoptotic and vascular cell markers on the sequential transplant biopsies. Treatment with eculizumab resulted in a rapid and dramatic improvement of the graft function in all three patients and in improvement of the TMA lesions within the graft. None of these patients had TMA flares after eculizumab was withdrawn. At the time of TMA diagnosis, immunofluorescence studies revealed intense C5b‐9 and C4d depositions at the endothelial cell surface of the injured vessels. Moreover, C5b‐9 colocalized with vessels exhibiting a high rate of apoptotic cells. Examination of sequential biopsies during eculizumab therapy showed that TMA lesions, C4d and apoptotic markers were rapidly cleared but the C5b‐9 deposits persisted for several months as a footprint of the TMA. Finally, we noticed that complement inhibition did not prevent the development of the chronic vascular changes associated with APSN. Eculizumab seems to be an efficient method for treating severe forms of posttransplant TMA due to APSN recurrence. Terminal complement inhibition does not prevent the development of chronic APSN. Abstract : In this study, the authors report successful treatment with eculizumab in patients with posttransplant thrombotic microangiopathy related to antiphospholipid syndrome resistant to plasmapheresis, and explore complement deposition in associated biopsies.